An analysis of twenty years' experience with operations for carcinoma of the stomach. - White, R R (1975)
We analyzed the records of 242 consecutive patients with adenocarcinoma of the stomach operated on for cure. We correlated survival with several factors, including the type of primary lesion, the operation performed, operative mortality, state of regional lymph nodes, margins of the resected specimens, and duration of preoperative symptoms. Overall survival at 5 years was only 18.6% and at 10 years was 7.1%. Patients with small malignant gastric ulcers, however, enjoyed increased survival at 5 years (53.8%) and at 10 years (15.0%). Overall operative mortality was 7.1%, but was 0% for patients with small malignant gastric ulcers. Even with large or high-lying lesions, radical operation can be accomplished with acceptable mortality and definite chance for cure. Thirteen of 45 five-year survivors had positive lymph nodes, and 7 of the 45 had positive margins of resection. Longer symptomatic preoperative periods, correlated positively with increased survival. Thirty patients with preoperative symptomatic periods exceeding 24 months had a 30.0% 5-year survival. Perhaps some of these lesions underwent malignant change in areas of symptomatic benign disease. We advocate early operation for gastric ulcers which do not heal promptly and stay healed.